A Critical Review of Properties and Analytical Methods for the Determination of Docetaxel in Biological and Pharmaceutical Matrices. (2nd November 2018) - da Silva, Gilmar Hanck; Fernandes, Mariza Aires; Trevizan, Lucas Noboru Fatori; de Lima, Felipe Tita; Eloy, Josimar O.; Chorilli, Marlus
ABSTRACT: Docetaxel (DTX) is an antineoplastic agent of the second generation of the taxoid family. It is a semi-synthetic drug prepared from a precursor extracted of the plant Taxus baccata . The commercial formulation of DTX, Taxotere®, employs the surfactant polysorbate 80, due to the low water solubility of the drug, causing several side effects. Therefore, there is a need to develop delivery systems to reduce the side effects of DTX. In addition, this drug has been qualitative and quantitatively analyzed in pharmaceutical formulations and biological samples. Thus, several techniques and analytical methods have been reported with the aim of optimizing the analytical signal, increasing sensitivity, selectivity and reducing the effects of interference. Herein, we highlight immunoassay, capillary electrophoresis and chromatographic methods. This review presents a summary of physicochemical and pharmacokinetics properties, mechanisms of action, drug delivery systems and analytical methods used in quantification of DTX in diverse matrices such as blood, plasma, oral fluid, urine, carcinoma cells, pharmaceutical formulations and delivery systems.